Status of Acquired Land Rights of the Cirebon Kasepuhan Palace in the Swapraja Land Case Against the Cirebon City Government - Maheswari, Adine Alimah (Jurnal Scientia Indonesia, 2021)
The establishment of the Basic Regulations on Agrarian Principles or Law Number 5 of 1960 (UUPA) regarding land, especially the regulation in the Fourth Dictum Letter A regarding autonomous lands and former autonomous lands, has caused many conflicts on the status of acquisition of land rights. Since the enactment of the regulation, the land status of the Keraton Kasepuhan Cirebon was declared state-owned by the Cirebon City Government because the land was previously autonomous or ex-self-governing land, but Keraton Kasepuhan Cirebon did not accept this statement. This study aims to determine the status of the land status of the Keraton Kasepuhan Cirebon and regarding the resolution of conflicts between the two parties. The method used in this research is normative juridical through a legal and conceptual approach. The data source used is secondary data through a study through the laws and regulations of books, journals, articles, and other sources. In this study, it was found that the land status of the Keraton Kasepuhan Cirebon was included in the Wewengkon land or land passed down from their ancestors and not included in the category of autonomous land or former autonomous land. Supposedly, the government can be more assertive regarding further regulations on land that is included in the category of self-governing land or former self-governing land, as well as regulate ulayat rights in a clear and detailed manner. This is intended to prevent conflicts over the status of land rights within the community and the state.